Epistemology of Laduni Science on Muhammad Al-Ghazali Thought - Ismail Suardi Wekke; Acep Aam Amiruddin; Moh. Wardi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
In essence, epistemology is a combination of thinking rationally and thinking empirically. This way of thinking is combined in the study of natural phenomena to discover the truth, the mind and the senses. Therefore, epistemology is an attempt to interpret and prove the belief that we know another fact, other than ourselves. The purpose of this research is to discover the workings and concepts of epistemology of science according to Al-Ghazali? And how the acquisition of knowledge and truth through Laduni science. The results showed that Al-Ghazali thought that Laduni science came from God directly into the human soul, the perfect soul of a clean and ready soul to muwajahah with God, that is where the science of God will be radiated. There are several methods to acquire laduni science. First, through the search of all the science and the most perfect part of a large number of available. Second, through the method of riyadhah and muraqabah. Third, through the method of reflection (tafakur). Fourth, through the method of inspiration. Fifth, through the tazkiyat an-Nafs method, the purification of the human soul through takhalli and tahalli stages. Sixth, through the method of zikr.